A NIR ratiometric fluorescent probe for the 'naked-eye' detection of endogenous hypochlorous acid in practical samples. Issue 13 (14th March 2019) - Xiong, Kangming; Huo, Fangjun; Zhang, Yongbin; Wen, Ying; Yin, Caixia
Abstract : We designed a near-infrared ratiometric (2.1 to 15.3, I 608 / I 735 ) fluorescent probe with a quick response (20 s) based on cyanine polyene derivatives. This probe can detect endogenous hypochlorous acid in HepG-2 cells and determine the hypochlorous acid content in 84 disinfectant and other actual samples. Abstract : Hypochlorous acid (HClO), as one of the reactive oxygen species (ROS), is very important to the human immune system. Although many hypochlorous acid fluorescent probes have been developed, most of them are not suitable for detecting endogenous HClO due to their own limitations such as a slow response time and short emission wavelength. In this work, we designed a near-infrared ratiometric (2.1 to 15.3, I 608 / I 735 ) fluorescent probe with a quick response (20 s) based on cyanine polyene derivatives. The system could detect endogenous hypochlorous acid in HepG-2 cells. It is significant that the color change in the measurement process makes the probe applicable to the determination of hypochlorous acid content in an 84 disinfectant and other actual samples.